Interactive tool SMART kapp in modern education - Yu. O. Dekhtiarova (Academy of Cognitive and Natural Sciences, 2017)
One of the effective ways in organizing education with informational technologies and media education is a productive use of SMART Education and cloud technologies. The aim of this research is to disclosure the essence of modern educational SMART kapp tool, which is built on principle includes cloud technology. The objectives of the research are to analyze the principle of SMART kapp; to identify opportunities to use it in the classroom. The object of research is the modern educational process. The subject of research is modern tools used for teaching in higher education. The author analyzed the native and foreign experience. It is established that due SMART kapp training participants can take part in training, brainstorming, or presentations regardless of location. Using the tool SMART kapp, which is built on a cloudy principle in modern educational process is an effective tool for collaboration and information visualization. The results of the research will be used to train future teachers of Informatics to use modern technology in professional activities.